DIABETES MELLITUS AMONG TUBERCULOSIS PATIENTS IN A TERTIARY CARE HOSPITAL OF LAHORE - Usmani, Rabia Arshed; Nasir, Muhammad Ijaz; Wazir, Salim; Pervaiz, Zarabia; Zahra, Taskeen; Akhtar, Mehwish (Journal of Ayub Medical College Abbottabad, 2014)
Background: Diabetes is an important risk factor for Tuberculosis (TB) that might affect disease presentation and treatment response but has hitherto been neglected by the clinicians. There is inadequate data on the prevalence of diabetes mellitus (DM) among TB patients in Pakistan. This study was conducted to determine the frequency of TB patients having DM. Methods: In this cross-sectional study, 158 TB patients admitted in Gulab Devi hospital were selected by systematic random sampling technique and data were collected using a pretested questionnaire. All patients underwent anthropometric measurements and baseline investigations. Diabetes was confirmed by determining fasting blood sugar level using cut-off value of 126 mg/dl. Data was entered in Epi-Data-6 and analyzed using Epi-Info. Results: Among 158 patients of tuberculosis, 41 (25.9%) were found to be diabetic, out of which 9 (5.69%) were newly diagnosed with diabetes. Moreover 96 (60.8%) patients were 35-55 years of age. Male patients were 97 (61.4%). Most of the patients belonged to the rural area 118 (74.7%) while 115 (72.8%) patients were illiterate and 139 (88%) had monthly income less than 7000 PKR. Conclusion: The study concludes that among tuberculosis patients with diabetes mellitus, about 5.69% were newly diagnosed during the course of investigation. This raises the concern that importance is not being given to routine screening of tuberculosis patients for diabetes by the clinicians. Health professionals should be updated about the link between diabetes and TB. Keywords: Diabetes mellitus, tuberculosis, socio-demographic characteristics, concomitant diabetes